Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
The solution of the equation is (2, 1).
x=2 and y=1
What do you meant by equation?
A mathematical assertion that two expressions are equal is known as equating. It can be expressed as either an identity, in which case the variables can take on any value, or a conditional equation, in which case the variables can only have specific values (roots).
According to the given information:
We have two options for finding the answer. The first is to solve the equations via term elimination:
x + 3y = 5 ..............1
x - 3y = -1 ...............2
2x = 4 ..............3
With the equation, we can determine x. (3)
x = 4/2
x = 2
To determine y, we may now swap out x=2 in equation (1).
x + 3y = 5
2 + 3y = 5
3y = 3
y = 1
We've discovered x and y now.
x=2
y=1
The second method involves removing x from equation 1.
x + 3y = 5
x = 5 - 3y
In the equation right now, we may substitute x = 5 - 3y......... (2)
x - 3y = -1
(5 - 3y) - 3y = -1
5 - 6y = -1
6y = -6
y = 1
Currently, we can change y=1 in equations (1), (2), or (4) to find x.
We'll apply the equation (1)
x + 3y = 5
x + 3(1) = 5
x + 3 = 5
x = 2
The two variants x = 2 and y = 1 have allowed us to confirm this.
To know more liner equation visit:
https://brainly.com/question/2995422
#SPJ4
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.